A Comparative Electrochemical Study of Arsenic Removal from Organic and Inorganic Sources using Various Sacrificial Electrodes - Jewel Andrew Gomes (The Minerals, Metals and Materials Society, 2010)
Arsenic is considered as one of the toxic materials being controlled by Environmental Protection Agencies in several developed and developing countries. It is found in the nature as constituents of the soil, minerals and also in various organic forms. It enters the air, water, and land from wind-blown dust and gets into water from runoff, leaching, soil erosion and anthropogenically from chemicals used for wood preservation, insecticides, medicine, military purpose, pigments, and electronic circuitries. There are several techniques available for removal of Arsenic, such as coagulation/filtration, lime softening, ion exchange, reverse osmosis, nanofiltration, wet chemical, and electrochemical. Electrocoagulation has been found as one of the most efficient techniques to remove inorganic arsenic with more than 99% efficiency. In this paper, we present our work on electrochemical treatment of both the inorganic and organic arsenic from water using various sacrificial electrode materials, i.e., iron, aluminum, copper, and combination of them. The floc produced by this method has been also characterized using XRD, SEM/EDS, FTIR, and cyclic voltammetry.